Professional Microsoft SQL server 2008 administration - Knight, Brian 1976- (Wrox professional guides, 2009)
This book is a how-to guide for experienced DBAs. The book is loaded with unique tips, tricks and workarounds for handling the most difficult SQL Server admin issues, including: managing and monitoring SQL Server, automating administration, security, change management, performance tuning, scaling and replication, clustering, backup and recovery.